1987
DOI: 10.1002/art.1780300702
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration and maturation within rheumatoid nodules

Abstract: In long-established rheumatoid nodules, monocytes continue to be recruited and to migrate from the outer vascular zone toward the palisade and central necrotic area. Maturation of these cells is shown to take place during tissue migration. We found that the great majority of palisade cells express exclusive mononuclear phagocyte phenotypes. Among this mononuclear phagocyte population are many cells that bear the receptor for iC3b (CR3), but few that bear the receptor for C3b (CR1). HLA-D region molecule expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Hedfors et al first reported that these cells stained positively with anti-HLA-DR and OKMl antibodies, in the manner of macrophages (9). Similar results have since been obtained in 3 other laboratories, using other monocyte/macrophage-specific monoclonal antibodies and anti-HLA-DR antibody (7,8,10,11).…”
Section: Radially Arranged Palisade Of Cellssupporting
confidence: 60%
See 1 more Smart Citation
“…Hedfors et al first reported that these cells stained positively with anti-HLA-DR and OKMl antibodies, in the manner of macrophages (9). Similar results have since been obtained in 3 other laboratories, using other monocyte/macrophage-specific monoclonal antibodies and anti-HLA-DR antibody (7,8,10,11).…”
Section: Radially Arranged Palisade Of Cellssupporting
confidence: 60%
“…Palmer et a1 have observed that the majority of these large mononuclear cells carry a monocyte marker (7) and acquire a macrophage marker in the immediate vicinity of the palisaded layer (8). Almost all of these monocyte/macrophage-staining cells are also HLA-DR+ (8-1 1).…”
Section: Outer Connective Tissue Zonementioning
confidence: 99%
“…In rheumatoid nodules macrophages migrate towards a central necrotic focus [1]. Altered expression of macrophage surface molecules [1,2] and production of angiotensin converting enzyme (ACE) [3] and IL-l^S [4] provide evidence of macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…In rheumatoid nodules macrophages migrate towards a central necrotic focus [1]. Altered expression of macrophage surface molecules [1,2] and production of angiotensin converting enzyme (ACE) [3] and IL-l^S [4] provide evidence of macrophage activation. The earliest foci of necrosis occur within small collections of macrophages characterized by sustained expression of the p8,14 molecule [5], a calcium binding dimer of unknown function [6].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Histologically, the RN is a granuloma in which activated macrophages are prominent. [9][10][11] Although RNs are not frequently encountered in RA patients, their existence strongly indicates RA diagnosis. In fact, Gossec et al [12] reported their diagnostic sensitivity as 2.4% and their specificity as 100%, and this is also true in cases of early RA.…”
mentioning
confidence: 99%